PENERAPAN PEMBERIAN TERAPI INHALASI NEBUL DENGAN PNEMONIA PADA ANAK DI RSD K.R.M.T WONGSONEGORO SEMARANG - Astuti, Tri; Boediarsih, Boediarsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Background : Pneumonia is inflammation or infection of the lung parenchyma, usually associated with filling the alveoli with fluid. Pneumonia is caused by viruses, bacteria (mycoplasma), fungi, parasites, or aspiration of foreign substances. Pneumonia is characterized by symptoms of coughing and/or difficulty breathing such as rapid breathing and inward pulling of the lower chest wall. Patients with pneumonia are in a state of dyspnea and cyanosis because of the presence of pneumonia and the amount of mucus in the bronchi/lungs. In order for the patient to be able to breathe smoothly, the mucus must be removed by sucking the mucus on the baby and to meet O2 needs, it needs to be assisted by giving O2 2L/minute on an ongoing basis. Purpose of the case study: To carry out the Application of Nebula Inhalation Therapy with Pumonia in Children at RSD K.R.M.T Wongsonegoro Semarang. Method : Case study report conducted in March 2023 for 3 days. The implementation provided is in accordance with IDHS, SIKI and SLKI. Results: Evaluation on client 1 based on the criteria that the researchers compiled from three nursing diagnoses that were upheld, there was 1 diagnosis that had not been resolved on day 3, namely the diagnosis of ineffective airway clearance. There were no data found for the other two diagnoses. Whereas on client 2 there were nine nursing diagnoses that were enforced, three nursing diagnoses could be resolved properly according to the nursing action plan, namely ineffective airway clearance, impaired gas exchange, and ineffective breathing pattern. Conclusion: The results of this study are expected to be input and as concrete evidence regarding the application of nursing care in families with cases of pneumonia in children in the family.